PERLUNYA SISTEM ADMINISTRASI PERTANAHAN YANG ANDAL DAN TRANSPARAN: MEMBANGUN KEPASTIAN HUKUM, PENYELESAIAN SENGKETA YANG ADIL, DAN MENDUKUNG INVESTASI SERTA AKSES USAHA - Albert Yansen; Al-Amin (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
A reliable and transparent land administration system is a key prerequisite for the creation of fair, efficient, and sustainable agrarian governance. This study aims to analyse the urgency of reforming the land administration system in Indonesia in order to achieve legal certainty, fair dispute resolution, and support investment and business access. Using a descriptive qualitative approach through policy analysis and literature study, this study found that weak data validity, overlapping ownership, and lack of transparency are the main root causes of problems in land management. The digitisation and integration of land information systems have proven to improve data accuracy, accelerate the dispute resolution process, and provide certainty of rights for the community and business actors. In addition, legal certainty over land contributes directly to improving the investment climate and ease of doing business, especially for sectors that depend on land ownership such as industry, infrastructure, and MSMEs. Therefore, comprehensive reforms covering regulatory, institutional, and information technology aspects are needed to strengthen the national land administration system to be more accountable, transparent, and inclusive.